A System to Test the Performance of RFID-Tagged Objects - Mallinson, Hugo; Hodges, Steve; Thorne, Alan (Proceedings of the 2007 International Symposium on Applications and the Internet Workshops (SAINTW'07), 2007)
A system is described which has been developed to assess how well RFID-tagged products can be read with various positionings of the tag on the product face. The system can search the entire product surface and provide a measure of tag performance in any location, allowing also for variation in the position of the reader antenna. Simulation of moving products is also possible. Results are shown.